Examining EFL Teachers’ Views on the Effects of Tests on English Teaching and Learning in Secondary Schools - AKPACA, SERVAIS MARTIAL (My University, 2020)
Tests should reflect teachers’ observations, classroom discussions and analysis of students’ work. The aim of this paper is to check whether these components are taken into account in the actual classroom tests organised in EFL classes in Benin. To this end, this paper uses a descriptive and quantitative approach to examine EFL in-service teachers’ views on the effects of tests on English teaching and learning. As a matter of fact, 100 inservice EFL teachers, i.e. 20 teachers per school, have been selected at random in five secondary schools in the Mono and Couffo regions, namely CEG1 Lokossa, CEG Comé, CEG1 Grand-Popo, CEG Djakotomey and CEG1 Azovè. On average, 80 percent of the questionnaires distributed have been filled and returned. The analyses carried out subsequently indicate that students poor performance in English tests is due to the lack of training for teachers as well as to the large class sizes and the lack of knowledge in test development and administration procedures. Furthermore, the lack of didactic materials in schools and students’ low motivation also contribute to their poor performance. The implications of this situation have been elucidated in a bid to enable various stakeholders to act to solve the problem.
Keywords: EFL; tests; in-service teachers; secondary school students; Mono and Couffo; regions